(3ecGJHI fUQ CHh GdaJhMs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3hUd cJGH GdTjN GdaGVd CWGd Gddg HbGAg hCOGe JCjjOg hfYeGFg hhbafG Ydjg hagefG LejY heG PcQg hMeOfG Gddg Ydi SdGeJg s
(3BNQgG (B:s
(3hbO hgH eG ajgG ef GdGdI def jbhi Ydi eWGdHJge hdG jXdege hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B93s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds